Cohort-based learning to transform learning in graduate public health: key qualitative findings from a pilot study - Akhtar, Sumreen; Gao, Yi; Keshwani, Ariz; Neubauer, Leah C. (Frontiers in Education, 2024)
In recent years, the idea that cohorts can prepare public health students for successful careers and professional development has been increasingly studied by researchers and educators. Previous literature suggests that cohorts can improve learning outcomes by providing students with mentorship and higher-order thinking assignments that model the real world and 21st century competencies—e.g. collaborative assignments, writing-intensive courses, and enrichment activities. The objective of this study is to explore the impacts of cohort-based learning on graduate student educational outcomes. The cohort structure can create a sense of collaboration and support, which in turn may maximize student success, engagement, and content retention. For the purposes of this study, MPH alumni (n = 13) who participated in a cohort model in a graduate global public health class provided insightful reflections through a qualitative survey. Responses via the survey indicated that cohort-based learning allowed students to feel more connected to the program and each other, fostering a collaborative and welcoming environment in the classroom. This was useful in developing critical thinking skills, greater learning experiences, and the ability to work in a variety of communities as reported by the participants, reflecting today's rapidly evolving society. Overall, alumni reported a positive experience with their cohort model, emphasizing more diversity in learning and thinking, personal enrichment, and professional development, which is consistent with the literature. This paper expands the knowledge on the utility and implications of cohort learning, a high-impact practice, in academic public health.